Regulation of viral replication by host restriction factors - Lin, Ying; Zhu, Yun; Jing, Ling; Lei, Xiaobo; Xie, Zhengde (Frontiers in Immunology, 2025)
Viral infectious diseases, caused by numerous viruses including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), influenza A virus (IAV), enterovirus (EV), human immunodeficiency virus (HIV), hepatitis B virus (HBV), and human papillomavirus (HPV), pose a continuous threat to global health. As obligate parasites, viruses rely on host cells to replicate, and host cells have developed numerous defense mechanisms to counteract viral infection. Host restriction factors (HRFs) are critical components of the early antiviral response. These cellular proteins inhibit viral replication and spread by impeding essential steps in the viral life cycle, such as viral entry, genome transcription and replication, protein translation, viral particle assembly, and release. This review summarizes the current understanding of how host restriction factors inhibit viral replication, with a primary focus on their diverse antiviral mechanisms against a range of viruses, including SARS-CoV-2, influenza A virus, enteroviruses, human immunodeficiency virus, hepatitis B virus, and human papillomavirus. In addition, we highlight the crucial role of these factors in shaping the host-virus interactions and discuss their potential as targets for antiviral drug development.